2013
DOI: 10.1007/s00125-013-2985-y
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of obesity-susceptibility loci on metabolic traits: a meta-analysis of up to 37,874 individuals

Abstract: Aims/hypothesis Genetic pleiotropy may contribute to the clustering of obesity and metabolic conditions. We assessed whether genetic variants that are robustly associated with BMI and waist-to-hip ratio (WHR) also influence metabolic and cardiovascular traits, independently of obesity-related traits, in meta-analyses of up to 37,874 individuals from six European population-based studies. Methods We examined associations of 32 BMI and 14 WHR loci, individually and combined in two genetic predisposition scores (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…GRB14/COBLL1 is a locus that has been shown to associate with a range of traits. [96], even after adjusting for obesity measures [97]. These associations are in concordance with a general pleiotropic metabolic risk profile affecting many of components of the metabolic syndrome in a clinically unfavourable direction.…”
Section: Genetic Overlap Of Obesity and Type 2 Diabetes: Epidemiologisupporting
confidence: 54%
See 3 more Smart Citations
“…GRB14/COBLL1 is a locus that has been shown to associate with a range of traits. [96], even after adjusting for obesity measures [97]. These associations are in concordance with a general pleiotropic metabolic risk profile affecting many of components of the metabolic syndrome in a clinically unfavourable direction.…”
Section: Genetic Overlap Of Obesity and Type 2 Diabetes: Epidemiologisupporting
confidence: 54%
“…A recent meta-analysis of data on up to~37,000 individuals systematically evaluated metabolic pleiotropic associations for BMI-and WHR-associated variants [97]. Analysis of individual variants revealed that some were associated with a metabolically unhealthy profile whereas others displayed more complex associations [97].…”
Section: Metabolically Healthy Vs Metabolically Unhealthy Associationmentioning
confidence: 99%
See 2 more Smart Citations
“…For each individual i we calculated BMI polygenic scores, using an additive genetic model, as the sum across k SNPs of the product of the β weight for the effect of that SNP on BMI by the individual’s allele count for that SNP: GRSnormali=Σk=1#SNPsβnormalknormalallele countnormali.k In exploratory analyses, we assigned each gene to one of four functional categories to generate mechanism-specific subscores after a literature review in PubMed: adipogenesis (adipocyte differentiation and fat accumulation, e.g. rs3817334 (MTCH2) with HDL-cholesterol levels[21]), appetite (regulation of appetite and food intake, e.g. rs10767664 (BDNF) with total caloric intake[22]), cardiopulmonary factors (cardiomyogenesis, oxidative stress response and cardiac remodeling, e.g.…”
Section: Methodsmentioning
confidence: 99%